A robust DEA-centric location-based decision support system for expanding recreovía hubs in the City of Bogotá (Colombia) (2017)
Multi-sectorial community programs to promote healthy living in public spaces are crucial for building a "culture of health" and could contribute to achieving the specific 2030 agendas of Sustainable Development Goals including reduction of inequalities, provision of inclusive, safe, resilient and sustainable cities and promotion of just, peaceful and inclusive societies. In this context, the Recreovía program of Bogotá (Colombia) provides physical activity classes in parks mainly for vulnerable communities. Here, we address the challenge of efficiently locating new Recreovía hubs and to do this, we develop a robust DEA-centric location-based decision support system (DSS) for guiding the Institute of Sports and Recreation of District of Bogotá on locating the best hubs to expand the Recreovía program throughout the city. This DSS Will serve as a model for analytics-based decision making for expanding equivalent programs in other cities.